Sistem Informasi Penjualan Ban Pada PT. Putra Jisko Vulkanisir Rantauprapat Berbsais Web - Setiawan, Nurul (Journal of Computer Science and Information System(JCoInS), 2021)
This website is expected to facilitate the search of PT. Putra Jisko Vulcanizing Data, making it easier to see sales and stock results, and able to cover a very broad world of markets from before. As well as one of the conditions for taking the Final Assignment Examination at the Labuhan Batu Computer Information Management (AMIK) Academy. The programming language used in making the system in question is using PHP and MySQL. Application Creation of the database using MySQL, Phpmyadmin Localhost. The preparation of this Final Project begins with Formulating problems, Identifying problems, Determining Objectives and Benefits in Gathering data from agencies, and explaining how the sales process takes place ,. After all the data needed is obtained, then proceed to the System Analysis Process. The results of the program are aimed at completing the Web-based Tire Sales Information System at PT. Putra Jisko Vulcanization. Hopefully with this sales system, it can improve performance in the inputting process and search sales data and the marketing process of PT. Putra Jisko Retreading Rantauprapat.